Role of matrix metalloproteinases in the pathogenesis of childhood gastroenteritis. Issue 8 (20th January 2016) - Kawamura, Yoshiki; Gotoh, Kensei; Takeuchi, Nao; Miura, Hiroki; Nishimura, Naoko; Ozaki, Takao; Yoshikawa, Tetsushi
Abstract : Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) have been implicated in the pathogenesis of gastrointestinal diseases, such as rotavirus gastroenteritis (GE). Kinetics of these biomarkers were examined in paired serum samples collected from bacterial enteritis patients with Campylobacter (n = 2) and Salmonella (n = 4) and viral GE patients with rotavirus (n = 27), norovirus (n = 25), and adenovirus (n = 11). At the time of hospital admission, all viral GE patients demonstrated increased MMP‐9 and decreased MMP‐2 and TIMP‐2 serum levels. In contrast to viral GE patients, serum MMP‐9 levels were not elevated at the time of hospital admission but elevated at the time of discharge; serum MMP‐2 and TIMP‐2 levels were decreased both at the time of admission and discharge in bacterial enteritis patients. Interestingly, the kinetics of serum MMP‐2, MMP‐9, and TIMP‐2 levels were similar among the viral GE patients but distinct from bacterial enteritis patients. Thus, the involvement of MMPs and TIMPs in the pathophysiology of gastrointestinal symptoms likely varies depending on the etiological agent. Further studies are required to verify whether the extent of the bacterial enteritis or age of the patients influences these serum biomarkers. J. Med. Virol. 88:1341–1346, 2016 . © 2016 Wiley Periodicals, Inc.